2017
DOI: 10.3906/sag-1510-40
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of primary gastric diffuse largeB-cell lymphoma: a single center study from Turkey

Abstract: Background/aim: Diffuse large B-cell primary gastric lymphomas (DLBC-PGLs) are treated with different therapies. Their optimal treatment is not well documented. Materials and methods:We retrospectively analyzed the data of 51 patients diagnosed with DLBC-PGL in the previous 10 years. All patients were treated with R-CHOP as first line. Radiotherapy was added to chemotherapy in 8 patients. Surgery was performed in 5 patients.Results: The median follow-up time of the 51 patients was 45.5 (range 5-144) months and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Patients present with non-specific symptoms such as abdominal pain and weight loss. 2,5 BL is a highly aggressive and curable type of lymphoma, with one-third of cases diagnosed between the ages of five and nine. The endemic type BL usually occurs as a result of Epstein-Barr virus (EBV) infection and most frequently involves the jaw bone.…”
Section: Discussionmentioning
confidence: 99%
“…Patients present with non-specific symptoms such as abdominal pain and weight loss. 2,5 BL is a highly aggressive and curable type of lymphoma, with one-third of cases diagnosed between the ages of five and nine. The endemic type BL usually occurs as a result of Epstein-Barr virus (EBV) infection and most frequently involves the jaw bone.…”
Section: Discussionmentioning
confidence: 99%
“…However, no specific prognostic factors have been identified including the International Prognostic Index (IPI), because most patients were at low-or low-intermediate clinical risk and will be considered as low risk; other factors such as deep of invasion, tumor burden, lymph node invasion, and molecular profile have not been validated. [4][5][6][7][8][9][10][11][12][13][14][15] The use of combined treatments such as surgery, radiotherapy, and chemotherapy did not show any benefit in this setting of patients, [3][4][5][6][7][8][9][10][11] and the addition of rituximab is controversial; 4,5 in our experience, the addition of rituximab to CHOP chemotherapy does not improve outcome. 16 Some years ago, we performed a retrospective clinical study and found that patients with elevated serum levels of lactic dehydrogenase (LDH) and beta 2 microglobulin (B2M) (>2 of normal levels) have a worse prognosis, independent of other prognostic factors.…”
Section: Introductionmentioning
confidence: 85%
“…Although clinical factors known to correlate with disease outcome in newly diagnosed PG-DLBCL have been described earlier, including molecular studies, most of these factors have not been validated on independent studies. 9,10,13,14,15 Thus, it is very difficult to draw any specific factors that can define a better treatment in this type of neoplasm. PG-DLBCL, at early stage, is generally sensitive to standard chemotherapy, because > 90% can achieve CR; 2,3,11 however, relapse can occur in 20–35%, and in most require aggressive salvage treatments.…”
Section: Discussionmentioning
confidence: 99%